A Review of Literature on the Involvement of Children from Indigenous Communities in Anglo Child Welfare Systems: 1973-2018 - Sinha, Vandna; Caldwell, Johanna; Paul, Leah; Fumaneri, Paulo Roberto (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
A series of recent legal and policy developments in Canada have potential to contribute to reconciliation efforts, particularly related to the overrepresentation of Indigenous children in child welfare systems. However, systematic collection, analysis, and synthesis of research knowledge—particularly, research that is locally grounded—on Indigenous child welfare involvement is notably missing from these efforts. With the aim of collating existing research knowledge on this topic, this scoping review of literature includes a broad swath of literature spanning decades (1973-2018) and countries with similar settler colonial histories (Canada, the United States, Australia, and New Zealand). Our search yielded 881 unique research publications. There was an increase in the number of publications over time in all four countries and a trend toward more empirical literature than non-empirical literature. We found that a plurality of publications focused on programs and services (n = 191), and policy or legal (n = 168) themes. While our review highlights a large base of literature on Indigenous child welfare involvement, it also illustrates the limits of the academic literature in representing the knowledge and experience of Indigenous Peoples and the need for more comprehensive synthesis and broader dissemination of the research related to Indigenous child welfare. These limitations restrict the extent to which existing research can inform the meaningful development of Indigenous child welfare policy in Canada. Due to these gaps, we advocate sustained investment in efforts to synthesize diverse sources of knowledge, support for open source publications, and structural support for Indigenous control of knowledge collection and dissemination regarding policy development related to their communities.